2015
DOI: 10.1530/eje-14-0941
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sleep quality and depression associate with decreased quality of life in patients with pituitary adenomas

Abstract: Objectives: Several studies reported decreased quality of life (QoL) and sleep as well as increased rates of depression for patients with pituitary adenomas. Our aim was to explore to what extent differences in depression and sleep quality contribute to differences in QoL between patients with pituitary adenomas and controls. Design: A cross-sectional case-control study. Setting: Endocrine Outpatient Unit of the Max Planck Institute of Psychiatry, Munich, Department of Internal Medicine, Ludwig-Maximilians-Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…This QoL impairment is worse in women (73). Additionally, sleeping difficulties namely increased slow-wave sleep compared to healthy controls may also impair QoL in prolactinoma patients (6,74).…”
Section: Prolactinomamentioning
confidence: 99%
“…This QoL impairment is worse in women (73). Additionally, sleeping difficulties namely increased slow-wave sleep compared to healthy controls may also impair QoL in prolactinoma patients (6,74).…”
Section: Prolactinomamentioning
confidence: 99%
“…We see that impaired sleep quality in pituitary adenomas reduces the quality of life of the patient and leads to problems that can lead to depression (14). Leistner et al reported they evaluated the deteriorating performance of patients whose quality of life was impaired due to sleepiness during the day in patients who underwent pituitary adenoma surgery and there was no statistically significant difference between them and normal healthy individuals (14). In 2014, Barbosa et al conducted polysomnography in their study of 35 patients at the 6 th month controls and found that prolactinoma and hypogonadism were the predisposing factors for the obstructive sleep apnea in this study and that the sleep quality was deteriorated after medical treatment due to developing obesity in these patients with sleepiness affecting the daytime performance (2).…”
Section: █ Discussionmentioning
confidence: 96%
“…We see that impaired sleep quality in pituitary adenomas reduces the quality of life of the patient and leads to problems that can lead to depression (14). Leistner et al reported they evaluated the deteriorating performance of patients whose quality of life was impaired due to sleepiness during the day in patients who underwent pituitary adenoma surgery and there was no statistically significant difference between them and normal healthy individuals (14).…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sometimes cortisol or prolactin levels do not correlate with disease severity, previous studies have implicated both prolactin and cortisol on human behaviour with multiple psychosomatic implications . For example, reduction in hippocampus volume, with progressive cognitive decline, increased risk of developing psychiatric illnesses such as depressive symptoms, anxiety‐related disorders and borderline personality disorder . Also, higher cortisol levels have been significant related to poor self‐esteem, low internal locus of control, loneliness and sleep deprivation; while reduction in serum cortisol has been related to positive affect demonstrated after aggregating momentary experiences throughout a working or leisure day .…”
Section: Discussionmentioning
confidence: 99%